Pengolahan Air Limbah Untuk Pemanfaatan Sebagai Flushing Toilet di Restoran, Bar, dan Klub Malam W Kota Surabaya - Tuhu Agung Rachmanto; M.Yureico Soobirumbassa U.K Yureico (Prosiding ESEC, 2023)
The current development factor is that restaurants, bars and night clubs are increasingly developing in big cities, one of which is the city of Surabaya. W's business activities, which are engaged in the restaurant, bar and nightclub business in Surabaya, produce domestic wastewater originating from kitchen, sink, dish washing and bathroom activities. The volume of clean water required to meet these needs is 7.86 m3/day at peak hours. The waste water produced from this activity is 5.28 m3/day and will be managed and used for flushing toilets. The levels of contaminants contained in wastewater such as COD, BOD, TSS and oil and grease must be adjusted to the wastewater quality standards listed in PERMEN LHK Number P.68 of 2016. Wastewater is treated using grease trap and biofilter technology to obtain outlet water. that meets water quality standards. The final water outlet has a water discharge of 3.37 m3/day while the water requirement for flushing the toilet is 2.38 m3/day. Therefore, the remaining unused outlet water will be stored in a storage tank and will later be handed over to a third party. Utilizing the results of wastewater treatment as flushing toilets can save the use of clean water for domestic clean water needs